2003
DOI: 10.1116/1.1565345
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam induced surface amorphization and sputter processes

Abstract: Focused ion beam techniques are among the most important tools for the nanostructuring of surfaces. As the physical phenomena during milling are not fully understood yet, we have applied the phase imaging capabilities of tapping mode atomic force microscopy to the investigation of surface amorphization, sputtering, and redeposition caused by focused ion beam irradiation. We have performed single spot as well as large area (20ϫ20 m 2 ) irradiation of silicon ͑100͒ wafers. We describe the localized formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Moreover, debris or contaminations between the electrodes and incompatibility with the existing microelectronics technology etc. also make barriers for the rapid progress of molecular devices . Hence, new method for nanogap electrodes fabrication is needed as a potential supplementary to the existing methods to avoid such drawbacks.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Moreover, debris or contaminations between the electrodes and incompatibility with the existing microelectronics technology etc. also make barriers for the rapid progress of molecular devices . Hence, new method for nanogap electrodes fabrication is needed as a potential supplementary to the existing methods to avoid such drawbacks.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Reflectivities of more than 80% are expected for optimized waveguide geometry with an increased overlap between the optical mode profile and the grating geometry. In FIB-defined microstructures the implanted Ga + ions are known to give rise to strong additional optical losses [25] through absorption and/or resulting local amorphization of the crystalline material [26]. In this study the interaction of the optical mode with the implanted region was decreased and only a small percentage of the mode intensity was exposed to the Ga + -implanted region.…”
Section: Laser Performancementioning
confidence: 97%
“…In addition, local composition and phase changes may occur. Numerous studies have been performed to assess these effects and, even though some of these are not directly related to TEM sample preparation, they do provide a good insight into the secondary effects of FIBs (Basnar et al, 2003). Brezna et al (2003) used scanning capacitance microscopy to measure the damage beneath FIB cuts in silicon and reported that the electrical properties were affected up to 600 nm beneath the surface.…”
Section: Fib Artifactsmentioning
confidence: 99%